Radiological Findings of Bezoars: A Case Report - Altunrende, Şerife Sevil; Canana, Arzu; Aydın, Mehmet Maruf; Gürel, Safiye (Fırat University, 2012)
Bezoars are formations (concreations) which develop mostly in gastrointestinal system originated from exogen or endogen sources. Patients are commonly asymptomatic or they have severe clinical outcomes as acute intestinal obstructions. Today, various alternative methods of treatment are being tested, but surgical removal is still the most valid and reliable method. By using radiological methods, bezoars could be diagnosed before the complications have occurred. We have presented four different gastric bezoar cases in pediatric and adult patients who have different etiologies in order to discuss radiological findings of bezoars. All of the patients examined with abdominal CT and one with abdominal MRI also.

Bezoarlar; en sık gastrointestinal sistemde farklı içeriğe sahip ekzojen veya endojen kaynaklı gelişen oluşumlardır. Asemptomatik seyredebilecekleri gibi akut intestinal obstruksiyonlar gibi daha ağır klinik tablolara yol açabilir. Günümüzde tedavide çeşitli alternatif yöntemler denenmektedir ancak hala en geçerli ve güvenilir yöntem cerrahidir. Radyolojik yöntemler kullanılarak komplikasyonlar gelişmeden önce bezoar tanısı konulabilmektedir. Bezoarların radyolojik görünümlerini tartışmak amacıyla farklı etiyolojilere sahip pediatrik ve erişkin yaş gurubunda dört ayrı gastrik bezoar olgusunu ele aldık. Olgularımızdan dördüne de tüm abdomen BT incelemesi, bir tanesine ayrıca üst abdomen MRG incelemesi yapıldı.
Bezoarların Radyolojik Bulguları: Olgu Sunumu